Eco-Friendly Remediation: Tea Leaves and Fibres as Adsorbents for High Cobalt Concentrations; Thermodynamics, Isotherms and Kinetic Studies - E. Etim, Emmanuel; Yakubu, Shedrach; C. Onaji, Emmanuel (Asian Journal of Environmental Research, 2024)
Increasing industrialization has produced huge amounts of liquid effluents, which are a key source of ecological unrest in diverse ecosystems. The high toxicity level of cobalt in surface water has drawn a lot ofattention; hence,a low-cost adsorbent made from leaves and fibres of Camellia sinensis has been developed to remove cobalt from wastewater. The kinetics of the pseudo-first and second-order sorption interaction, as well as the physicochemical parameters of the precursor adsorbent, was investigated. There was a linear relationship between Cobalt uptake and biosorbent dosage under ideal conditions; the optimum dosage was 4 g. Between 10 to 40 minutes of contact time, clearance of cobalt was greater than 90 per cent. The Gibb’s free energy (∆Go) at various temperatures ranges from -9980 to -1020, indicating a spontaneous system, viable for both parts of the precursor adsorbent. The entropy change (∆So) was found to be +31.05 and +35.12 for tea leaves and fibre respectively, implying a highly disordered biosorption interface. The enthalpy (∆Ho) was found to be-8.58 and -10.03 for tea leaves and fibres hence, an exothermic system was suggested by the enthalpy with a second order kinetics. Therefore, Camellia sinensis is a suitable adsorbent for the effective removal of high cobalt concentrations in wastewater.